Single cell atlas of canine natural killer cells identifies distinct circulating and tissue resident gene profiles - Razmara, Aryana M.; Lammers, Marshall; Judge, Sean J.; Murphy, William J.; Gaskill, Cameron E.; Culp, William T.N.; Gingrich, Alicia A.; Morris, Zachary S.; Rebhun, Robert B.; Brown, C. Titus; Vail, David M.; Kent, Michael S.; et al. (Frontiers in Immunology, 2025)
IntroductionNatural killer (NK) cells in mice and humans are key effectors of the innate immune system with complex immunoregulatory functions, and diverse subsets have been identified with distinct characteristics and roles. Companion dogs with spontaneous cancer have been validated as models of human disease, including cancer immunology and immunotherapy, and greater understanding of NK cell heterogeneity in dogs can inform NK biology across species and optimize NK immunotherapy for both dogs and people.MethodsHere, we assessed canine NK cell populations by single-cell RNA sequencing (scRNAseq) across blood, lung, liver, spleen, and placenta with comparison to human NK cells from blood and the same tissues to better characterize the differential gene expression of canine and human NK cells regarding ontogeny, heterogeneity, patterns of activation, inhibition, and tissue residence.ResultsOverall, we observed tissue-specific NK cell signatures consistent with immature NK cells in the placenta, mature and activated NK cells in the lung, and NK cells with a mixed activated and inhibited signature in the liver with significant cross-species homology.DiscussionTogether, our results point to heterogeneous canine NK populations highly comparable to human NK cells, and we provide a comprehensive atlas of canine NK cells across organs which will inform future cross-species NK studies and further substantiate the spontaneous canine model to optimize NK immunotherapy across species.